2022
DOI: 10.1029/2022sw003215
|View full text |Cite
|
Sign up to set email alerts
|

CME Evolution in the Structured Heliosphere and Effects at Earth and Mars During Solar Minimum

Abstract: The activity of the Sun alternates between a solar minimum and a solar maximum, the former corresponding to a period of “quieter” status of the heliosphere. During solar minimum, it is in principle more straightforward to follow eruptive events and solar wind structures from their birth at the Sun throughout their interplanetary journey. In this paper, we report analysis of the origin, evolution, and heliospheric impact of a series of solar transient events that took place during the second half of August 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 140 publications
(174 reference statements)
0
25
0
Order By: Relevance
“…The events we selected represent a few unique scenarios for forecasters: Event 1 is a stealth CME, Event 2 is a limb eruption as seen by SDO, Event 3 is close to the limb but seen by both SDO and STEREO-A, and Event 4 is completely on the Sun's far side. Analyzing case studies from a variety of sources with respect to Earth's viewpoint (while assuming that observations of the photospheric magnetic field are only available from Earth) is extremely beneficial for future CME predictions across the whole heliosphere (e.g., Shiota et al 2014;Palmerio et al 2022a)-considering, e.g., the increasing interest in space weather at Mars (e.g., Lee et al 2017;Luhmann et al 2017;Palmerio et al 2022b), it is not unreasonable to expect that forecasts over the next decade(s) will include information for other planets and/or for crews on deep-space travel. As we have shown in this study, in the OSPREI model, the type of magnetogram and PFSS source surface height the end-user chooses will affect both the coronal deflection/rotation and MFR prediction of the CME in a more or less significant way.…”
Section: Discussionmentioning
confidence: 99%
“…The events we selected represent a few unique scenarios for forecasters: Event 1 is a stealth CME, Event 2 is a limb eruption as seen by SDO, Event 3 is close to the limb but seen by both SDO and STEREO-A, and Event 4 is completely on the Sun's far side. Analyzing case studies from a variety of sources with respect to Earth's viewpoint (while assuming that observations of the photospheric magnetic field are only available from Earth) is extremely beneficial for future CME predictions across the whole heliosphere (e.g., Shiota et al 2014;Palmerio et al 2022a)-considering, e.g., the increasing interest in space weather at Mars (e.g., Lee et al 2017;Luhmann et al 2017;Palmerio et al 2022b), it is not unreasonable to expect that forecasts over the next decade(s) will include information for other planets and/or for crews on deep-space travel. As we have shown in this study, in the OSPREI model, the type of magnetogram and PFSS source surface height the end-user chooses will affect both the coronal deflection/rotation and MFR prediction of the CME in a more or less significant way.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to have the Solar Orbiter magnetically connected to the shock if the solar wind speed is low. Since there is no available solar wind plasma data for Solar Orbiter during the event, Palmerio et al (2022) estimated the solar wind speed based on the data from Magnetometer and the Radio and Plasma Waves instrument on board Solar Orbiter using a deHoffmann-Teller analysis. These authors showed that there is likely a transition of solar wind speed from a low-speed stream to a high-speed stream at the onset of SEPs in their Fig.…”
Section: Time-intensity Profilesmentioning
confidence: 99%
“…Despite the fact that many observational studies have been devoted to this event, a range of comprehensive modeling efforts on this SEP event are still lacking. Very recently, Palmerio et al (2022) simulated the CME and the SEP event using the WSA-Enlil-SEPMOD modeling combo. Their model calculation suggested that significant enhancements of SEP intensity at the onset of the event only exist at PSP.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, two of the three strongest geomagnetic storms of Solar Cycle 24 (in terms of the Dst index) were due to a CME immediately followed by a HSS. These are the 17 March 2015 storm, strongest of the cycle with the Dst index reaching −234 nT (e.g., Kataoka et al., 2015), and the 26 August 2018 storm, third‐strongest of the cycle with the Dst index reaching −175 nT (e.g., Palmerio et al., 2022). The second‐strongest storm, on 23 June 2015 and with the Dst index reaching −198 nT, on the other hand, was driven by successive, interacting CMEs (e.g., Augusto et al., 2018).…”
Section: Introductionmentioning
confidence: 99%